MAENA DANCE, TOBACCO, AND NIGHT DANCE IN THE MARRIAGE CUSTOMS OF THE COASTAL MUSLIM COMMUNITY NIAS ISLANDS – INDONESIA - Deniansyah Damanik; Khatima Sarah Gea (Wahdatul Ulum Institute, 2026)
This study aims to analyze the marriage customs of coastal Muslims on the island of Nias which have differences with non-Muslim communities on the island of Nias. In addition, there is the Maena Dance, tobacco and also the night of ringing in the marriage customs of the coastal Muslim community of Nias island. This research method uses qualitative research by combining literature research and empirical studies. The results of the study show that there is a very significant difference between the non-Muslim marriage customs of the Nias archipelago and the marriage customs of the coastal Muslims of the Nias Islands, although there are still few similarities. The existence of the Maena Dance, tobacco and also the night of drumming are the result of the assimilation and cultural acculturation of the people of Nias, Aceh and also Minangkabau.